Pengaruh Komunikasi Internal Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Di Toko Maya Padang - Muhammad Rayhannul Hakim (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Human resources play an important role in the success of an organization, because human resources affect the quality of its workforce. This study aims to determine the effect of internal communication on employee performance at Toko Maya Padang, the effect of leadership style on employee performance, and the effect of internal communication and leadership style together. This study uses a quantitative approach to analyze the effect of individual characteristics and internal communication on work ethics in 33 employees of Toko Maya Padang. The results of data analysis indicate that internal communication and leadership style have a significant positive effect on employee performance at Toko Maya Padang. Partial hypothesis testing (t-test) shows that internal communication has a positive and significant effect on employee performance, while leadership style has a positive and significant effect.